The Role of Relational Reward Benefits for Developing the Non-Financial Value of a Customer to an Organization: Structural Equation Modeling Approach - Kristiani, Enny; Sumarwan, Ujang; Yuliati, Lilik Noor; Saefuddin, Asep (Gadjah Mada International Journal of Business, 2014)
Research on the customer value to an organization has been widely explored, yet most studies only determined on the financial value based on the customerâs purchasing behavior. The value of customers beyond their purchasing behavior âdefined as the relational worth - has not been commonly captured yet. This non-financial value is one of the drivers in retaining customers, hence it becomes a crucial factor in preserving the profitability of the organization. For this reason, this paper aims to examine the customer non-financial valuations of a loyalty reward program. The scope of the study covered a reward program involving consumer exertions in the context of a Frequent Flyer Program (FFP) offered by an airline in Indonesia. The hypotheses are empirically tested with a sample of FFP members conducted through an online survey (n=475). The data were statistically analyzed using structural equation modeling (SEM) as a first order construct. Results indicate that the perceived social rewards lead to an affective and normative commitment as well as consumersâ satisfaction, while the economic reward did not have an effect on developing affective bonds with members for long-term relationships. The relational benefit offered through the FFP creates affectively and normatively committed members who produce relational behaviors, in terms of WOM, immunity, openness and acquiescence of the members to the airline. Furthermore, the FFP members produced social behaviors toward the airline when they felt satisfied with their relational exchanges.Â Â Â Â Â Â Â Â Â Â